Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x4 - 4x3 - 8x2 + 8x
= x(x3 - 4x2 - 8x + 8)
= x[x3 + 8 - 4x(x + 2)]
= x[(x + 2)(x2 - 2x + 4) - 4x(x + 2)]
= x(x + 2)(x2 - 6x + 4)
= x(x + 2)(x2 - 6x + 9 - 5)
= \(x\left(x+2\right)\left[\left(x-3\right)^2-5\right]=x\left(x+2\right)\left(x-3+\sqrt{5}\right)\left(x-3-\sqrt{5}\right)\)
\(x^4-4x^3-8x^2+8x\)
\(=x\left(x^3-4x^2-8x+8\right)\)
\(=x\left(x^3-6x^2+2x^2+4x-12x+8\right)\)
\(=x\left[\left(x^3-6x^2+4x\right)+\left(2x^2-12x+8\right)\right]\)
\(=x\left[x\left(x^2-6x+4\right)+2\left(x^2-6x+4\right)\right]\)
\(=x\left(x^2-6x+4\right)\left(x+2\right)\)
\(=x\left[\left(x-3\right)^2-\left(\sqrt{5}\right)^2\right]\left(x+2\right)\)
\(=x\left(x-3-\sqrt{5}\right)\left(x-3+\sqrt{5}\right)\left(x+2\right)\)
\(x^3+5x^2+8x-4=x^3+x^2+4x^2+4x+4x+4\)
\(=\left(x^3+x^2\right)+\left(4x^2+4x\right)+\left(4x+4\right)\)
\(=x^2\left(x+1\right)+4x\left(x+1\right)+4\left(x+1\right)\)
\(=\left(x^2+4x+4\right)\left(x+1\right)\)
\(=\left(x+2\right)^2\left(x+1\right)\)
\(x^3-5x^2+8x-4\)
\(=x^3-4x^2-x^2+4x+4x-4\)
\(=\left(x^3-4x^2+4x\right)-\left(x^2-4x+4\right)\)
\(=x\left(x^2-4x+4\right)-\left(x^2-4x+4\right)\)
\(=\left(x-1\right)\left(x^2-4x+4\right)\)
\(=\left(x-1\right)\left(x-2\right)^2\)
Xong rùi đấy
`#3107`
`x^4 - 8x + 63`
`= x^4 + 4x^3 + 9x^2 - 4x^3 -16x^2 - 36x + 7x^2 + 28x + 63`
`= (x^4 + 4x^3 + 9x^2) - (4x^3 + 16x^2 + 36x) + (7x^2 + 28x + 63)`
`= x^2(x^2 + 4x + 9) - 4x(x^2 + 4x + 9) + 7(x^2 + 4x + 9)`
`= (x^2 + 4x + 9)(x^2 - 4x + 7)`
____
`64x^4 + y^4`
`= 64x^4 + 16x^2y^2 + y^4 - 16x^2y^2`
`= (64x^4 + 16x^2y^2 + y^4) - (16x^2y^2)`
`= [(8x^2)^2 + 2*8x^2*y^2 + (y^2)^2] - (4xy)^2`
`= (8x^2 + y^2)^2 - (4xy)^2`
`= (8x^2 + y^2 - 4xy)(8x^2 + y^2 + 4xy)`
____
`x^3 + 3xy`
`= x(x^2 + 3y)`
\(=x^2\left(x-1\right)-4\left(x-1\right)^2=\left(x-1\right)\left[x^2-4\left(x-1\right)\right]\\ =\left(x-1\right)\left(x^2-4x+4\right)=\left(x-1\right)\left(x-2\right)^2\)
= \(x^4-2x^3-6x^3+12x^2-x^2+2x+6x-12\)
= \(x^3\left(x-2\right)-6x^2\left(x-2\right)-x\left(x-2\right)+6\left(x-2\right)\)
= \(\left(x-2\right)\left(x^3-6x^2-x+6\right)\)
= \(\left(x-2\right)\left(x^2\left(x-6\right)-\left(x-6\right)\right)\)
= \(\left(x-2\right)\left(x-6\right)\left(x-1\right)\left(x+1\right)\)
x4 - 8x3 + 11x2 + 8x - 12
= (x3 - 7x2 + 4x + 12)(x - 1)
= (x3 - 8x + 12)(x + 1)(x - 1)
= (x - 6)(x - 2)(x + 1)(x - 1)
\(x^4+8x^3+28x^2+48x-13\)
\(=x^4+4x^3+13x^2+4x^3+16x^2+52x-x^2-4x-13\)
\(=x^2\left(x^2+4x+13\right)+4x\left(x^2+4x+13\right)-\left(x^2+4x+13\right)\)
\(=\left(x^2+4x-1\right)\left(x^2+4x+13\right)\)
x4+8x3+15x2-4x-2
= (x4+4x3+x2)+(4x3+16x2+4x)-(2x2+8x+2)
= x2.(x2+4x+1)+4x.(x2+4x+1) -2(x2+4x+1)
= (x2+4x+1).(x2+4x-2)
easy
\(\left(x^4+3\right)-8x\)
\(\sqrt{\left(x^4+3\right)}^2-\sqrt{8x}^2\)
\(\left(\sqrt{\left(x^4+3\right)}-\sqrt{8x}\right)\left(\sqrt{\left(x^4+3\right)}+\sqrt{8x}\right)\)